2005
DOI: 10.18061/dsq.v25i2.544
|View full text |Cite
|
Sign up to set email alerts
|

Empowering Indigenous Families who have Children with Disabilities: An Innovative Outreach Model

Abstract: Socially and legally it is acknowledged that families with children with disabilities are a critical component of any educational program or Individualized Education Plan (Yell, 2002). Indigenous families with children who have disabilities face unique additional challenges in working collaboratively with schools and education professionals. Parent Training and Information Centers started as a result of federally funded research on the needs of families of children with disabilities. The unique challenges face… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Part D of the IDEA governs the federal grants that are aimed toward enhancing school-based services for children with disabilities. This includes parent training and information centers which, along with the schools, are responsible for making sure families have the knowledge and skills to be active participants in the services their child receives at school (Banks and Miller, 2005). In Arizona, Raising Special Kids is the parent training and information center that serves the entire state; however, few families served identify as Indigenous (Raising Special Kids, 2021).…”
Section: Lesson Number and Titlementioning
confidence: 99%
“…Part D of the IDEA governs the federal grants that are aimed toward enhancing school-based services for children with disabilities. This includes parent training and information centers which, along with the schools, are responsible for making sure families have the knowledge and skills to be active participants in the services their child receives at school (Banks and Miller, 2005). In Arizona, Raising Special Kids is the parent training and information center that serves the entire state; however, few families served identify as Indigenous (Raising Special Kids, 2021).…”
Section: Lesson Number and Titlementioning
confidence: 99%
“…In the USA, although providing a valued service, F2Fs may not reach the families who need them the most, particularly those from culturally/linguistically diverse backgrounds (Banks and Miller, 2005;Klingner et al, 2007). McNamara et al (2003) reported that minority and low income families are more likely to act alone or with extended family rather than responding to collective parent networks.…”
Section: Purpose Of This Studymentioning
confidence: 99%
“…Moreover, Reed and Black (2006) believe that valuing diversity in the class mean learning about the differences and similarities and finding ways to work which will lead to developing a culturally responsive curriculum and cross cultural understanding to help students build self esteem. Furthering this concept, Banks and Miller (2005) illustrated the challenge and difficulties in cross-cultural communication. They also focused on the ongoing neglect of language, and the lack of culturally rich curriculum knowledge.…”
Section: Different Culturesmentioning
confidence: 99%
“…Rosenqvist (personal communication, April 18, 2008) his most significant challenge as an educator has been to reach "the diverse multicultural world." Banks and Miller (2005) also addressed these political issues of equity in both general and special education. Another study, focused on multicultural special education as an effective intervention for today's schools.…”
Section: Challengesmentioning
confidence: 99%
See 1 more Smart Citation